Analysis of the Influence of Product Quality and Price on the Decision to Purchase Red Bricks in Latuhalat Village, Ambon City - Siahainenia, Silfiena; Siahainenia, Ashwin (ProBisnis : Jurnal Manajemen, 2024)
This study aims to examine the effect of quality and price on purchasing decisions for red bricks from Latuhalat village, Ambon city. The population in this study were the people of Ambon city with a sample size of 103 respondents with accidential technique.The data analysis technique is multiple regression with the t test. The results of the study are product quality and price affect the decision to purchase bricks from Latuhalat village, Ambon city.